Comparative Genomic Analysis Reveals Genetic Variations in Multiple Primary Esophageal Squamous Cell Carcinoma of Chinese Population - Liang, Jinxiao; Wang, Yinjie; Cai, Lei; Liu, Jinshi; Yan, Junrong; Chen, Xin; Wu, Xiaoying; Chen, Qixun (Frontiers in Oncology, 2022)
Esophageal squamous cell carcinoma (ESCC) is one of the most common and lethal malignant tumors. The incidence of malignant transformation of esophageal mucosa increases greatly due to long-term exposure to factors such as smoking, drinking, and poor eating habits. Furthermore, multiple primary tumors could occur synchronously or asynchronously in the upper aerodigestive tract, especially in the esophagus, adding difficulty to the treatment of ESCC. Genetic mutations are important during the malignant transformation from normal mucosa to esophageal cancer, but the underlying mechanism has not been fully elucidated. In this study, we used whole-exome sequencing (WES) to profile genetic variations in physiologically normal mucosa (PNM) and ESCC tumors, as well as PNM of non-ESCC subjects. We found significant differences in mutation frequencies of NOTCH1 and NOTCH2, copy number variations (CNVs) at both gene and chromosomal arm levels, and cancer-related HIPPO, WNT, and NRF2 signaling pathways between ESCC tumors and normal mucosa. Our analysis of both primary tumors and paired PNM in bifocal ESCC revealed three different primary tumor evolution modes, and the most common mode exhibited a complete genomic divergence in all the samples from the same patient. Furthermore, the mutation frequency of TP53 was significantly higher in ESCC cases than that in non-ESCC cases. Overall, our results provide important evidence for further elucidating the mechanisms of genetic mutations underlying the cause of ESCC.